Teachers’ Perspective on E-Learning Readiness in Junior High School: A Case Study in Indonesia - Irfan, Ade; Alfurqan, Alfurqan; N.H, Esty Saraswati; Safriana, Safriana (International Conference on Multidisciplinary Research, 2021)
This paper aimed to reveal the readiness of Junior High Schools in Banda Aceh and Jombang to implement e-learning based on the teacher's perspective through six factors of e-learning readiness, including student readiness factors, teacher readiness, infrastructure readiness, school culture readiness, and face-to-face learning tendencies. Data was collected through an online questionnaire, involving 69 students from various junior high schools. The findings of this study showed that the readiness for implementing e-learning in Junior High Schools in Banda Aceh and Jombang was at a score of 3.5 and was in the ready category but still needed improvement. Six factors were the basis for determining the readiness to implement e-learning, four of which were in the ready category but required a slight improvement of student readiness factor, teacher readiness factor, school culture readiness, and management readiness. While, the other two factors were in the unready category including the infrastructure readiness factor and readiness for face-to-face learning tendencies. Keywords: e-learning, readiness, teachers’ perspective, junior high school